MANAJEMEN PROGRAM MATRIKULASI BAHASA ARAB DI PONDOK PESANTREN DARUL HIKMAH KOTA BIMA - Nurfadila Rasyid; Zakiya Arifa; Ahmad Mubaligh (LP2M IAIN Sultan Amai Gorontalo, 2022)
The focus of this research is to describe the management of the Arabic matriculation program at Darul Hikmah Boarding School in Bima. In learning Arabic Darul Hikmah Boarding School implements a language matriculation program where this program must be followed by students and is expected to provide benefits in the field of language and convenience for students. In this paper the research used is qualitative research where data is collected through observation, interviews and documentation. In this paper the research used is qualitative research where data is collected through observation, interviews and documentation. Then in analyzing data consists of data collection as well as data reduction and conclusion drawing.The results of the study concluded that the series of arabic matriculation program management activities carried out at Darul Hikmah Boarding School included: planning an Arabic matriculation program through the establishment of learning programs, material preparation, media use and determination of learning method approaches. (2) Organizing Arabic matriculation has prepared qualified tutors with S2 and S1 Arabic qualifications as measured by teaching tests. (3) implementation of matriculation program applying time token arends learning model by using al-Arabiyatu Baina Yadai Auladina teaching book. (4) evaluation of Arabic matriculation program is to determine assessment standards, hold written and oral examinations, make improvements and follow-up. Thus the matriculation program using the learning time token arends model is a good program in managing the Arabic matriculation program at Darul Hikmah boarding school in Bima